Analisis Strategi Rantai Pasok dan Risiko untuk Menjaga Kestabilan Pengadaan Barang dan Jasa di Mixue - Azhar Berliana Putra Santosa; Aghas Pradana Muttaqien; Nisa Luthfiah Azzahra; Sigit Djalu Purwoko (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Mixue is a company that uses supply chain management as the main concept in procuring goods and services. The quality and quantity of these procurements have direct implications on operational efficiency, company reputation, and customer satisfaction. The development of the mixue company can be said to be quite rapid, this is supported by mixue which uses a franchise business concept which has a rapid growth impact which allows mixue to reach buyers widely. The aim of this research is to find out the extent of the supply chain strategy implemented by the mixue company and to find out the extent of the risks borne to maintain the procurement of goods and services in this company. The research method used in this writing is a qualitative method. The data taken in this research is secondary data in the form of the results of literature and literature studies carried out by the author. Supply Chain Management (SCM) plays a key role in Mixue's success. With efficient SCM, Mixue can keep transportation costs to a minimum and production quality maintained.